Factors Affecting Non-compliance With Planning Standards In The Residential Area Of Benghazi City, Libya - Abrabba, Saaed Awad (2023)
Planning standards refer to codes or regulations for space requirement, site specification, height and other criteria as required by the local authorities for purposes land and property development. Issues of non-compliance with planning standards have been reported in many developing countries with increased population growth and urbanization. To address the research gap between residents’ housing needs and existing planning standards, this research examines those factors that could affect the level of compliance with planning standards, specifically in the residential area of Benghazi City, Libya. This research develops a conceptual framework based on bibliometric and systematic literature approaches to identify five major factors that affect compliance with planning standards; they are administrative, legislation, social, economy and demography. This study employed a mixed-method design for data collection including a questionnaire survey among 359 heads of households and semi-structured interviews with four officials and planning authorities of Benghazi City, Libya Study results obtained using Warp PLS .6 software indicate lower level of compliance in Benghazi due to economic factors, such as shortage of housing schemes and housing loans; factors of inappropriate standards of plot size to accommodate large household size; administrative factors of inefficient monitoring and enforcement of the planning standards; and social factors of lack of awareness on the importance of planning standards. Planning authorities in Benghazi City should re-examine current residential standards to allow better understanding and make these standards more appropriate to match the residents’ socio-economic conditions.